2011
DOI: 10.1093/brain/awr070
|View full text |Cite
|
Sign up to set email alerts
|

NG2 expressed by macrophages and oligodendrocyte precursor cells is dispensable in experimental autoimmune encephalomyelitis

Abstract: Increased expression of the chondroitin proteoglycan NG2 is a prominent feature in central nervous system injury with unknown cellular source and biological relevance. Here, we describe the first detailed analysis of experimental autoimmune encephalomyelitis in NG2 knockout mice and NG2 knockout bone marrow chimeras. We show that both macrophages and oligodendrocyte progenitor cells express and secrete NG2 in response to transforming growth factor-β. A subpopulation of macrophages expresses NG2 within leucocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 50 publications
1
46
3
Order By: Relevance
“…The latter finding might induce a slight upregulation of [ 11 C]NE40 on the contralateral side, which might explain why no GFAP+ cells were co-labeled with CB2. The immunostaining finding that CB2-colabelled NG2+ cells were found to be round in shape suggested that they were monocytes and played a protective role [43]. In contrast, NG2+ cells without co-labeling with CB2 were thought to be oligodendrocyte precursor cells insensitive to CB2.…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding might induce a slight upregulation of [ 11 C]NE40 on the contralateral side, which might explain why no GFAP+ cells were co-labeled with CB2. The immunostaining finding that CB2-colabelled NG2+ cells were found to be round in shape suggested that they were monocytes and played a protective role [43]. In contrast, NG2+ cells without co-labeling with CB2 were thought to be oligodendrocyte precursor cells insensitive to CB2.…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with a higher expression of inducible nitric oxide synthase (iNOS), IL-1β and TNF-α, which could be reversed by treatment with NG2 siRNA. In addition, neuroinflammatory disorders, such as autoimmune encephalomyelitis, elevate the expression of NG2 in OPCs, macrophages and CNS-resident microglia, which is mediated by transforming growth factor-beta (TGF-β) [35, 36]. Inhibition of TFG-β activity by decorin [37, 38] or TGF-β1 receptor signaling by SB525334 attenuates this TGF-β-induced NG2 expression [39].…”
Section: Introductionmentioning
confidence: 99%
“…These cells, also known as synantocytes or oligodendrocyte precursor cells, are the most actively cycling population of cells in the normal brain, both rodent and human [41,53], and are also the most actively cycling population after various brain lesions, including cortical stab wound injury [63,83], demyelinating lesions induced by anti-GalC antibodies [79] and in experimental autoimmune encephalitis, an animal model of multiple sclerosis [54,106]. This increase in proliferation is caused by a reduction in cell cycle length and recruitment of quiescent NG2+ cells [141].…”
Section: Fate Restricted Progenitor Cells In the Adult Brainmentioning
confidence: 99%